Fatality rate, risk factors, and functional decline in peritoneal dialysis patients with coronavirus disease 2019: A nationwide cohort study - Chuengsaman, Piyatida; Boongird, Sarinya; Dandecha, Phongsak; Hemachudha, Thiravat; Nopsopon, Tanawin; Kanjanabuch, Talerngsak; Sritippayawan, Suchai; Kantachuvesiri, Surasak (Frontiers in Medicine, 2022)
Background: The fatality rates and factors associated with death from coronavirus disease 2019 (COVID-19) in hemodialysis patients have been extensively investigated. Whist those data on peritoneal dialysis (PD) patients are scarce. Methods: In this nationwide cohort study, we assessed the 28-day COVID-19-related fatality rate in PD patients between August 2021 and July 2022 using data from the InCov19-PD registry. Predictors associated with death were evaluated using an age-adjusted Cox regression model. Changes in functional status before and during COVID-19 were also examined. Results: A total of 1487 eligible participants were evaluated. During the study period, 196 participants died within 28 days after COVID-19 diagnosis (case fatality rate: 13%). In an age-adjusted Cox regression model, the number of COVID-19 vaccines administered [adjusted hazard ratio (HR) 0.69, 95% confidence interval (CI) 0.55–0.87], functional impairment during COVID-19 (HR 2.46, 95% CI 1.59–3.81), SARS-CoV-2 infection with the Delta variant (HR 2.22, 95% CI 1.56–3.13), the need for respiratory support (HR 7.13, 95% CI 3.74–13.57), and the absence of corticosteroid therapy (HR 0.72, 95% CI 0.54–0.97) were associated with an increased risk of death within 28 days after COVID-19 diagnosis (p <0.05 for all). The number of functionally independent PD patients dropped from 94% at baseline to 63% during COVID-19 (p <0.01). Conclusions: The COVID-19-related 28-day fatality rate was high among PD patients. The predictors of COVID-19-related death in PD patients were similar to those in hemodialysis patients. During COVID-19, PD patients commonly experienced a functional decline.